The Association of Adiposity Indices and Plasma Vitamin D in Young Females in Saudi Arabia - Lubna Ibrahim Al Asoom (International Journal of Endocrinology)
Background. Vitamin D deficiency is a global health problem. Some evidences indicate its association with metabolic syndrome, type II diabetes, and cardiovascular diseases. In the current study we aim to study the association of vitamin D level and indicators of adiposity in young Saudi females. Subjects and Methods. 87 young healthy Saudi females were recruited from University of Dammam, Dammam, Saudi Arabia. Each subject filled vitamin D questionnaire and had exercise stress test to determine VO2 peak. Body weight, BMI, waist and hip circumference, and ratios were determined. Blood was analyzed for 25-OH vitamin D, glucose, triglycerides, total cholesterol, and differential cholesterol. Results. 25-OH vitamin D/body weight was negatively associated with waist circumference and waist/stature ratio. No significant difference was found between the groups of BMI with regard to the data of questionnaire or 25-OH vitamin D/body weight. Obese and overweight subjects had lower VO2 peak. Conclusion. In young Saudi females we found that the relative value of vitamin D to body weight is a better indicator of vitamin D status particularly in obese subjects and it is negatively associated with adiposity measures of waist circumference and waist/stature ratio.